2013
DOI: 10.1002/wrcr.20400
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between hyporheic flow produced by stream meanders, bars, and dunes

Abstract: [1] Stream channel morphology from grain-scale roughness to large meanders drives hyporheic exchange flow. In practice, it is difficult to model hyporheic flow over the wide spectrum of topographic features typically found in rivers. As a result, many studies only characterize isolated exchange processes at a single spatial scale. In this work, we simulated hyporheic flows induced by a range of geomorphic features including meanders, bars and dunes in sand bed streams. Twenty cases were examined with 5 degrees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
153
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(159 citation statements)
references
References 49 publications
6
153
0
Order By: Relevance
“…This approach relies either on the delineation of characteristic zones (e.g., bars vs. channels), on rules that define spatial patterns, or on process based models of erosion/deposition (see Koltermann and Gorelick 1996). Examples of topographic reconstruction applied to channels are provided by Legleiter et al (2011), Casas et al (2010b, and in the context of GSI modeling, by Stonedahl et al (2013).…”
Section: Generating a Demmentioning
confidence: 99%
“…This approach relies either on the delineation of characteristic zones (e.g., bars vs. channels), on rules that define spatial patterns, or on process based models of erosion/deposition (see Koltermann and Gorelick 1996). Examples of topographic reconstruction applied to channels are provided by Legleiter et al (2011), Casas et al (2010b, and in the context of GSI modeling, by Stonedahl et al (2013).…”
Section: Generating a Demmentioning
confidence: 99%
“…The exchange of water between surface and subsurface flows, generally termed hyporheic exchange, plays a critical role in structuring fluvial ecosystems [Boulton et al, 1998;Aubeneau et al, 2015]. Several studies have shown that fractal topography can produce scaling in hyporheic residence time distributions [Stonedahl et al, 2012[Stonedahl et al, , 2013Gomez-Velez and Harvey, 2014]. Worman et al [2006Worman et al [ , 2007 used numerical experiments to demonstrate the link between fractal topography and water storage times.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the influence of bedrock geology at the catchment scale (Section 3.2), superficial sediments can significantly impact GSE via the HZ (Krause et al, 2012) and in turn influence overall hyporheic exchange flows and storage (e.g., presence of low conductivity streambed strata, Bencala, 1984;Harvey and Wagner, 2000;Buffington and Tonina, 2009;Angermann et al, 2012a;Stonedahl et al, 2013). At this scale, bed material caliber (grain size) expresses internal channel-20 forming mechanisms framed in the degree of confinement of the valley (Table 2).…”
Section: Hydrogeological Factors In River and Floodplain Typementioning
confidence: 96%
“…Valley-floor and channel morphology control HEF in different ways depending on the valley type, which can be related generally to stream order because of covariations between channel constraints, channel planform morphology, and bedform sequences (Stonedahl et al, 2013;Kasahara and Wondzell, 2003) (Fig. 8).…”
Section: Valley Typementioning
confidence: 99%
See 1 more Smart Citation